2016
DOI: 10.1186/s12864-016-2886-9
|View full text |Cite
|
Sign up to set email alerts
|

OGS2: genome re-annotation of the jewel wasp Nasonia vitripennis

Abstract: BackgroundNasonia vitripennis is an emerging insect model system with haplodiploid genetics. It holds a key position within the insect phylogeny for comparative, evolutionary and behavioral genetic studies. The draft genomes for N. vitripennis and two sibling species were published in 2010, yet a considerable amount of transcriptiome data have since been produced thereby enabling improvements to the original (OGS1.2) annotated gene set. We describe and apply the EvidentialGene method used to produce an updated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 101 publications
2
40
0
Order By: Relevance
“…To determine the venom composition of these four species, we generated proteomes from the venom reservoir, which stores venom prior to injection into the host, and assembled de novo transcriptomes from the venom gland plus reservoir. These data are compared to existing [3032] and our de novo expression and genome data (see STAR Methods for details).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the venom composition of these four species, we generated proteomes from the venom reservoir, which stores venom prior to injection into the host, and assembled de novo transcriptomes from the venom gland plus reservoir. These data are compared to existing [3032] and our de novo expression and genome data (see STAR Methods for details).…”
Section: Resultsmentioning
confidence: 99%
“…For whole body adult transcriptomes, any contigs with expression <2 FPKM were removed. Contigs were ranked from 1 to n based on highest to lowest FPKM and assigned annotations by BLASTp to N. vitripennis genome [30] (OGS2 http://arthropods.eugenes.org/genes2/nasonia/genes/) and NCBI nr database (accessed Feb, 2014). RNAseq produced high quality transcriptomes with each library averaging 97.7% of their reads >90 bp, 44% GC content, and a Phred score of 37.…”
Section: Star Methodsmentioning
confidence: 99%
“…Many insects with less sophisticated social behavior have larger genomes, with a greater number of functional protein‐coding genes. Among species within the Hymenoptera, which generally have smaller genomes than species in other holometabolous orders, the eusocial Argentine ant ( Linepithema humile ) has a genome size of about 251 Mb and 16,123 protein‐coding genes (Smith et al, ) and the solitary parasitoid wasp Nasonia vitripennis has a genome 295.78 Mb in size, with approximately 24,388 annotated genes (Rago et al, ), almost 36 more genes per Mb than the honey bee.…”
Section: Introductionmentioning
confidence: 99%
“…A). This was considerably smaller than the predicted size of 11.4 kDa for the translated messenger RNA (mRNA) sequence based on de novo transcriptome assembly from venom reservoirs (Martinson et al ., ) and the gene model from the N. vitripennis official gene set (Rago et al ., ). We sequenced the ~5 kDa fragment, which confirmed that the band corresponds to a 5.55 kDa portion of the predicted VenY B protein.…”
Section: Resultsmentioning
confidence: 97%